2017
DOI: 10.4187/respcare.05360
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Pulmonary Vasodilators: Are There Indications Within the Pediatric ICU?

Abstract: Inhaled nitric oxide (INO) is only FDA-cleared for neonates (> 34 weeks gestation) with hypoxic respiratory failure-associated pulmonary hypertension. Off-label use of INO is common in the pediatric population despite a lack of evidence regarding survival benefit, questioning whether the therapy should be considered outside the neonatal period. A lack of definitive evidence combined with increasing health-care costs has led to the use of less costly inhaled prostacyclin as an alternative to INO, presenting uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…In terms of pharmacologic treatment, INO and its effects in improving VQ mismatch in the setting of pediatric ARDS has been studied. When INO is delivered to the respiratory tract, the principal effect occurs in adequately ventilated areas of the lung, producing localized short-term pulmonary vasodilation [ 10 ]. Research has shown that inhaled NO acutely improves oxygenation and decreases pulmonary vascular resistance in children with severe acute hypoxemic respiratory failure and ARDS [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of pharmacologic treatment, INO and its effects in improving VQ mismatch in the setting of pediatric ARDS has been studied. When INO is delivered to the respiratory tract, the principal effect occurs in adequately ventilated areas of the lung, producing localized short-term pulmonary vasodilation [ 10 ]. Research has shown that inhaled NO acutely improves oxygenation and decreases pulmonary vascular resistance in children with severe acute hypoxemic respiratory failure and ARDS [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It increases the concentration of cyclic adenosine monophosphate in vascular smooth muscle cells while INO produces cyclic guanosine monophosphate [ 18 ]. Prostacyclin also increases endogenous surfactant production, which is beneficial in ARDS because it may decrease the need for toxic ventilator settings by improving lung compliance [ 10 ]. Additionally, prostacyclin suppresses the synthesis of TNFα in activated monocytes, which is implicated in the pro-inflammatory state of ARDS [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a naturally occurring prostaglandin produced primarily by the endothelial cells of the vascular intima, and is well known as antiplatelet aggregation, potent vasodilator, cytoprotective effects. Inhaled prostacyclin or analogs can be offered as an alternative treatment option for PH patients, and include epoprostenol (Flolan, Veletri), iloprost (Ventavis), and treprostinil (Tyvaso) in clinical use (143,144).…”
Section: Prostacyclin or Analogsmentioning
confidence: 99%
“…Several small studies have evaluated the hemodynamic effects of continuously nebulized epoprostenol in children, 86 but only 1 study discussed its use for pediatric ARDS. 87 Dahlem et al 87 reported a 26% improvement in the oxygen index compared with the placebo cohort.…”
Section: Pediatric Ardsmentioning
confidence: 99%
“…Iloprost has a lower viscosity, greater stability, lower pH, and longer half-life than epoprostenol. 86 This makes iloprost superior for inhalation. In the pediatric acute care setting, iloprost dosing ranges from 0.5 to 5 mg/kg, 90,96 with 1 study reporting a single dose of 25 ng/kg/min for 10 min.…”
Section: Pharmacodynamics and Dosingmentioning
confidence: 99%